Resolving the High‐Latitude Ionospheric Irregularity Spectra Using Multi‐Point Incoherent Scatter Radar Measurements. Issue 9 (7th September 2022) - Goodwin, L. V.; Perry, G. W.
Abstract: To provide new insights into the relationship between geomagnetic conditions and plasma irregularity scale‐sizes, high‐latitude irregularity spectra are computed using a novel Incoherent Scatter Radar (ISR) technique. This new technique leverages: (a) the ability of phased array Advanced Modular ISR (AMISR) technology to collect volumetric measurements of plasma density, (b) the slow F‐region cross‐field plasma diffusion at scales greater than 10 km, and (c) the high dip angle of geomagnetic field lines at high‐latitudes. The resulting irregularity spectra are of a higher spatiotemporal resolution than what has been previously possible with ISRs. Spatial structures as small as 20 km are resolved in less than 2 minutes (depending on the radar mode). In this work, we focus on Resolute Bay ISR‐North (RISR‐N) observations operating in the "imaginglptight" mode. In addition to having an unprecedented view of the size and occurrence of irregularities as they traverse the polar cap, we find that as the F‐region plasma density decreases below approximately 2.5 × 10 10  m −3 at 350 km altitude the spectral power shifts to scale‐sizes lower than 50 km. Additionally, near magnetic local noon, the spectral power shifts to scales greater than 50 km, and from 15 to 6 magnetic local time, the spectral power shifts to scales lower than 50 km. This reflects the role of photoionization dominating high‐latitude ionospheric structuring in the polar cap. Key Points: A novel mapping technique is developed to compute high latitude ionospheric irregularity spectra at a high spatiotemporal resolution The spectral power shifts to structures smaller than 50 km at low plasma densities and from dusk to dawn Photoionization dominates structuring in the polar cap and creates structures 100 km and larger